2004
DOI: 10.1101/gad.1162404
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mammalian life span by the short isoform of p53

Abstract: Overexpression of the short isoform of p53 (p44) has unexpectedly uncovered a role for p53 in the regulation of size and life span in the mouse. Hyperactivation of the insulin-like growth factor (IGF) signaling axis by p44 sets in motion a kinase cascade that clamps potentially unimpeded growth through p21Cip1. This suggests that pathways of gene activity known to regulate longevity in lower organisms are linked in mammals via p53 to mechanisms for controlling cell proliferation. Thus, appropriate expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
575
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 544 publications
(606 citation statements)
references
References 47 publications
22
575
1
4
Order By: Relevance
“…It has, however, also been suggested that p53/47 behaves solely as an antagonist of p53-mediated growth suppression (Courtois et al, 2002). Although this appears contradictory and the underlying reasons are unclear, it reinforces the idea that the proportion of p53/47 to FLp53 has implications for the cell biological response to p53 activation, a view that is substantiated by a recent transgenic mouse model demonstrating that overexpression of p53/47 leads to p53-dependent cellular senescence and premature ageing (Maier et al, 2004). p53/47 might thus be a factor of weight in directing the balance of choices to one or the other set of p53-dependent cell stress responses.…”
Section: Introductionmentioning
confidence: 74%
“…It has, however, also been suggested that p53/47 behaves solely as an antagonist of p53-mediated growth suppression (Courtois et al, 2002). Although this appears contradictory and the underlying reasons are unclear, it reinforces the idea that the proportion of p53/47 to FLp53 has implications for the cell biological response to p53 activation, a view that is substantiated by a recent transgenic mouse model demonstrating that overexpression of p53/47 leads to p53-dependent cellular senescence and premature ageing (Maier et al, 2004). p53/47 might thus be a factor of weight in directing the balance of choices to one or the other set of p53-dependent cell stress responses.…”
Section: Introductionmentioning
confidence: 74%
“…Exceptions to the above are the p53/p44 and the AT‐1 sTg systems. In the case of p53/p44, the primary defect is in the N‐terminal regulatory functions of the p53 protein, which leads to reduced stemness potential of stem cells as well as hyperactivation of IGF‐1R signaling (Campisi, 2004; Lessel et al, 2017; Maier et al, 2004; Pehar, Ko, Li, Scrable, & Puglielli, 2014; Tyner et al, 2002). AT‐1 sTg mice display many features that are in line with classical segmental progerias, such as reduced growth, alopecia, skin lesions, rectal prolapse, osteoporosis, cardiomegaly, muscle atrophy, reduced fertility, and systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Knockin homozygote mice (p53 DNp53/DNp53 ), expressing only amino-truncated p53 proteins, are cancer-prone like p53 À/À mice, and do not show any accelerated aging phenotype, indicating that that is dependent on the effect in trans of DNp53 on wild-type p53. 67,68 Knockin heterozygote p53 mice (p53 þ /M ) expressing one mutant p53 allele, bearing a point mutation in the DNA binding domain, are as susceptible to cancer as heterozygote p53 þ /À mice but do not show any accelerated aging phenotype. 69,70 This indicates that DNp53 proteins and point mutant p53, mutated in the DNA-binding domain, act…”
Section: Biological Activities Of P53 and Its Isoformsmentioning
confidence: 99%